Thriving school climate and growth mindset leadership for sustainable well-being in elementary education - Muhamad Fajar Dismawan; Annisa Yulistia; Septian Dwi Putra; Handoko Handoko (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
The pursuit of sustainable school well-being constitutes an indispensable imperative in contemporary educational transformation, particularly within primary education, which must rigorously balance academic excellence with holistic development. Growth mindset leadership and a thriving school climate function as non-negotiable catalysts for institutional resilience, collaborative efficacy, and long-term academic flourishing. This study systematically examines the empirical literature to determine the structural relationships among growth-mindset leadership, a thriving school climate, and overarching school well-being in primary educational settings. Strictly adhering to the PRISMA 2020 guidelines, a rigorous Systematic Literature Review was executed across premier international and national academic databases. Thematic analysis dictates four definitive trends: a critical escalation of scholarly focus on post-pandemic school well-being; the decisive role of growth mindset leadership in driving educator motivation and an adaptive institutional culture; the empirical positive influence of a thriving climate on sustainable well-being; and the establishment of an integrated framework linking leadership, climate, and well-being as the absolute foundation of a robust school ecosystem. The findings unequivocally assert that sustainable school well-being is attainable exclusively through leadership paradigms that systematically cultivate intellectual growth, inclusivity, and a collective institutional purpose. Ultimately, this review establishes critical theoretical insights and authoritative policy implications, directing future research trajectories to align with national curricula and the Sustainable Development Goals (SDGs) for quality education.